Swimming performance is reduced by reflective markers intended for the analysis of swimming kinematics - Washino, S.; Mayfield, D. L.; Lichtwark, G. A.; Mankyu, H.; Yoshitake, Y. (Journal of Biomechanics, 2019)
The present study aimed to clarify whether swimming performance is affected by reflective markers being attached to the swimmer`s body, as is required for a kinematic analysis of swimming. Fourteen well-trained male swimmers (21.1 ± 1.7 yrs) performed maximal 50?m front crawl swimming with (W) and without (WO) 25 reflective markers attached to their skin and swimwear. This number represents the minimum required to estimate the body`s center of mass. Fifty meter swimming time, mid-pool swimming velocity, stroke rate, and stroke length were determined using video analysis. We found swimming time to be 3.9 ± 1.6% longer for W condition. Swimming velocity (3.3 ± 1.8%), stroke rate (1.2 ± 2.0%), and stroke length (2.1 ± 2.7%) were also significantly lower for W condition. To elucidate whether the observed reduction in performance was potentially owing to an additional drag force induced by the reflective markers, measured swimming velocity under W condition was compared to a predicted velocity that was calculated based on swimming velocity obtained under WO condition and an estimate of the additional drag force induced by the reflective markers. The mean prediction error and ICC (2,1) for this analysis of measured and predicted velocities was 0.014 m/s and 0.894, respectively. Reducing the drag force term led to a decrease in the degree of agreement between the velocities. Together, these results suggest that the reduction in swimming performance resulted, at least in part, from an additional drag force produced by the reflective markers.